Supporting Family Caregivers of Advanced Cancer Patients: A Focus Group Study. Issue 5 (11th December 2017) - Nissim, Rinat; Hales, Sarah; Zimmermann, Camilla; Deckert, Amy; Edwards, Beth; Rodin, Gary
Abstract : Objective: As the first stage in developing an intervention for family caregivers of individuals with advanced cancer, we conducted a focus group study to understand their needs. Background: Family caregivers play an important role in the care of advanced cancer patients. Despite substantial burden and distress experienced by family caregivers of individuals with advanced cancer, their needs are not addressed systematically. Method: The study took place at a large urban cancer center in Canada. We conducted 2 focus groups: one with 7 current family caregivers, the other with 7 bereaved caregivers. Participants were asked about their support needs while providing care, how and when they preferred to receive support, and the perceived barriers and facilitators to addressing their support needs. Responses were analyzed using the conventional content analysis method. Results: Family caregivers wished for support in relation to 3 domains: decision‐making in the face of uncertainty, information about death and dying, and current and anticipated emotional distress. They identified 3 barriers to receiving support: the organization of cancer care around the patient, rather than the family; the timing of information provision; and caregivers' tendency to dismiss their own needs. Caregivers expressed a strong need for caregiver‐specific support. Conclusion: This study allowed us to identify caregiver‐perceived intervention needs, barriers to access and continuity of intervention, and suggestions for intervention design. Implications: This information is of value to inform the design of interventions for this population.